Ministry of Health Circular to Boards of Guardians, General Strike 1926 (page 3) (1926)
1926 "Ministry of Health Circular to Boards of Guardians, General Strike 1926 (page 3)" [T0614c.jpg], 1926, Ministry of Health This is the Ministry of Health Circular sent out to Boards of Guardians in England and Wales on 5 May 1926, advising them that it was unlawful to give unemployment benefit or other relief to strikers. The circular cites a Court of Appeal judgment in a case relating to Merthyr Tydfil, Wales in 1900. Guardians were allowed to help dependants of strikers if they were destitute, providing that half of the relief was in kind, i.e. communal meals.